ASUHAN KEPERAWATAN GERONTIK PADA NY. S DENGAN OSTEOARTHRITIS MELALUI PENERAPAN STRETCHING STATIC DAN DYNAMIC TERHADAP PENURUNAN INTENSITAS NYERI DI WILAYAH KERJA PUSKESMAS BELAKANG PADANG KOTA BATAM - Afif D Alba (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
The prevalence of osteoarthritis in the world is 18.7 million elderly in the world (Arthritis Foundation, 2020). The prevalence of joint disease in Indonesia is recorded at around 7.3% and osteoarthritis or arthritis is a common joint disease. The prevalence of OA by age in Indonesia is quite high, namely 5% at the age of 40 years, 30% at the age of 40-60 years, and 65% in the elderly over 61 years. The highest number of Arthritis sufferers was in the five Batam City Health Centers with the highest number being in the Sei Langka Health Center with 426 cases, and the Back Padang Health Center with 111 cases. This professional scientific paper aims to carry out gerontic nursing care for Mrs. S with Osteoarthritis through the application of static and dynamic stretching to decrease the intensity of knee pain in the working area of ​​the Puskesmas Rear Padang Batam. The method used in this professional scientific paper is a case study. The results of the study obtained that the client said pain in his right knee, in the morning he felt stiff, painful when moved and when he walked for too long, the patient looked stooped using a stick with the main nursing diagnosis, namely Acute Pain. The intervention and implementation provided was in the form of Static and Dynamic Stretching therapy for 14 days. The results of the final evaluation of nursing care for Mrs. S with Osteoarthritis that were obtained after the implementation of nursing were decreased pain levels, improved mobility disorders, and increased patient balance. Through Static and Dynamic Stretching therapy, it is hoped that Osteoarthritis sufferers can be one of the appropriate non-pharmacological therapies to help reduce the intensity of knee pain in the elderly.